Nations of emigrants : shifting boundaries of citizenship in El Salvador and the United States - Coutin, Susan Bibler (Cornell University Press, 2007)
The violence and economic devastation of the 1980-1992 civil war in El Salvador drove as many as one million Salvadorans to enter the United States, frequently without authorization. In Nations of Emigrants, the legal anthropologist Susan Bibler Coutin analyzes the case of emigration from El Salvador to the United States to consider how current forms of migration challenge conventional understandings of borders, citizenship, and migration itself. Interviews with policymakers and activists in El Salvador and the United States are juxtaposed with Salvadoran emigrants' accounts of their journeys to the United States, their lives in this country, and, in some cases, their removal to El Salvador. These interviews and accounts illustrate the dilemmas that migration creates for nation-states as well as the difficulties for individuals who must live simultaneously within and outside the legal systems of two countries. During the 1980s, U.S. officials generally regarded these migrants as economic immigrants who deserved to be deported, rather than as political refugees who merited asylum. By the 1990s, these Salvadorans were made eligible for legal permanent residency, at least in part due to the lives that they had created in the United States. Remarkably, this redefinition occurred during a period when more restrictive immigration policies were being adopted by the U.S. government. At the same time, Salvadorans in the United States, who send relatives more than.